2009
DOI: 10.1002/elan.200804389
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Arsenic(III) Using Platinum Nanoparticle‐Modified Screen‐Printed Carbon‐Based Electrodes

Abstract: The electrochemical detection of arsenic(III) was investigated on platinum nanoparticle-modified carbon-based screen-printed electrodes (PtNPs/SPCEs) in 1 M aqueous H 2 SO 4 . PtNPs/SPCEs were prepared by electrochemical deposition of K 2 PtCl 6 . The resulting electrode surfaces were characterized with scanning electron microscopy (SEM). By using the As(III) oxidation peak for the analytical determination, there is no interference from Cu(II) if present in contrast to the other metal surfaces typically used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(41 citation statements)
references
References 43 publications
(34 reference statements)
0
41
0
Order By: Relevance
“…2C, under optimized conditions, the As (0) Fig. 2C) and those in many reported analogues [19,20], and the E cp is more positive than those reported previously even at comparable pH [21][22][23].…”
Section: Resultsmentioning
confidence: 51%
“…2C, under optimized conditions, the As (0) Fig. 2C) and those in many reported analogues [19,20], and the E cp is more positive than those reported previously even at comparable pH [21][22][23].…”
Section: Resultsmentioning
confidence: 51%
“…Furthermore, nano or microparticle based electrode materials are known to offer improved performances toward arsenic sensing [8,[15][16][17][18]. More distinctly, it has been shown that the use of platinum [8,17,18], iridium [15], and cobalt oxide [16] nanoparticles modified electrodes results in better sensitivity than platinum macroelectrodes for arsenic sensing, by method of direct oxidation of As(III) to As(V) in the 0.7-0.8 V (vs. SCE) potential range. However, these rather high potentials are close to the water decomposition potential and may also cause serious interferences in the analysis from other metallic and organic species.…”
Section: Introductionmentioning
confidence: 99%
“…Platinum nanoparticles on screen printed electrodes (SPE) and boron doped diamond (BDD) electrodes were employed with detection limit of 5.68µg/L(Sanllorente-Méndez et al 2009) and 0.5µg/L(Hrapovic et al 2007) respectively. A detection limit of 0.1µg/L was achieved with platinum nanotube-array electrode(Xu et al 2008) Prakash et al, (2012).…”
mentioning
confidence: 99%